2015
DOI: 10.1128/jvi.03631-14
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hepatitis C Virus Genome Replication by Xrn1 and MicroRNA-122 Binding to Individual Sites in the 5′ Untranslated Region

Abstract: miR-122 is a liver-specific microRNA (miRNA) that binds to two sites (S1 and S2) on the 5= untranslated region (UTR) of the hepatitis C virus (HCV) genome and promotes the viral life cycle. It positively affects viral RNA stability, translation, and replication, but the mechanism is not well understood. To unravel the roles of miR-122 binding at each site alone or in combination, we employed miR-122 binding site mutant viral RNAs, Hep3B cells (which lack detectable miR-122), and complementation with wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
92
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 46 publications
1
92
0
Order By: Relevance
“…The ability of miR-122 to bind two sites presents unique points of regulation, where binding of miR-122 at individual or both sites, sequentially or cooperatively might modulate distinct steps in the HCV infectious cycle (Garcia-Sastre and Evans, 2013; Thibault et al, 2015). Jangra et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of miR-122 to bind two sites presents unique points of regulation, where binding of miR-122 at individual or both sites, sequentially or cooperatively might modulate distinct steps in the HCV infectious cycle (Garcia-Sastre and Evans, 2013; Thibault et al, 2015). Jangra et al .…”
Section: Discussionmentioning
confidence: 99%
“…Translation and replication of the HCV genome is directed by RNA elements within both UTRs. Interestingly, specific interactions of the liver-specific microRNA miR-122 with two binding sites in the 5′ UTR mask the 5′ end of the genome from Xrn1 and Xrn2 5′-to-3′ exonuclease digestion (Li et al, 2013, 2015; Sedano and Sarnow, 2014; Thibault et al, 2015), and thus contribute to maintaining HCV RNA abundance. While the binding of miR-122 to both sites 1 and 2 is critical (Jopling et al, 2008), the exact nature of these interactions remains elusive (Garcia-Sastre and Evans, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Further, significant attempts have been made to test potential use of miRs as therapeutic agents. MiR-122, the most abundant miR expressed in the liver, binds to the 5′-UTR of the Hepatitis C virus genome to positively affect RNA stability and replication (3). Therefore, inhibition of endogenous miR-122 shows efficacy in treating chronic Hepatitis C infection.…”
Section: Introductionmentioning
confidence: 99%
“…miR-122 is a major determinant of viral RNA replication, as it inhibits XRN1 from degrading the viral RNA, allowing accumulation, increased replication, and increased translation of viral RNA. Studies have shown that miR-122 only needs to be bound at one of the two sites for it to have this inhibitory effect, and binding to both sites maintains a co-operative effect, rather than increasing the effectiveness [52]. In addition to the miR-122 binding site, the 5'UTR HCV viral RNA includes four stem loops of which three (loops 2-4) appear to function as a highly structured internal ribosome entry site, allowing translation initiation of the viral RNA [50].…”
Section: Xrn1 and The Host Response To Virusesmentioning
confidence: 99%
“…Recent publications show that 5'-3' degradation of HCV transcripts is stalled by expression of miR-122 in the host cell, which binds via its miRNA seed sequence to the 5'UTR of the viral transcript ( Figure 2C). The association of miR-122/RISC, including Ago2 [51], at two sites in the 5' UTR, protects it from degradation by XRN1 [52]. miR-122 is a major determinant of viral RNA replication, as it inhibits XRN1 from degrading the viral RNA, allowing accumulation, increased replication, and increased translation of viral RNA.…”
Section: Xrn1 and The Host Response To Virusesmentioning
confidence: 99%